The ergogenic potency of carbohydrate mouth rinse on endurance running performance of dehydrated athletes - Kamaruddin, H. K.; Ooi, C. H.; Mündel, T.; Aziz, A. R.; Muhamed, A. M. C. (European Journal of Applied Physiology, 2019)
Purpose: To examine the effect of carbohydrate (CHO) mouth rinsing on endurance running responses and performance in dehydrated individuals. Methods: In a double blind, randomised crossover design, 12 well-trained male runners completed 4 running time to exhaustion (TTE) trials at a speed equivalent to 70% of VO2peak in a thermoneutral condition. Throughout each run, participants mouth rinsed and expectorated every 15 min either 25 mL of 6% CHO or a placebo (PLA) solution for 10 s. The four TTEs consisted of two trials in the euhydrated (EU-CHO and EU-PLA) and two trials in the dehydrated (DY-CHO and DY-PLA) state. Prior to each TTE run, participants were dehydrated via exercise and allowed a passive rest period during which they were fed and either rehydrated equivalent to their body mass deficit (i.e., EU trials) or ingested only 50 mL of water (DY trials). Results: CHO mouth rinsing significantly improved TTE performance in the DY compared to the EU trials (78.2 ± 4.3 vs. 76.9 ± 3.8 min, P = 0.02). The arousal level of the runners was significantly higher in the DY compared to the EU trials (P = 0.02). There was no significant difference among trials in heart rate, plasma glucose and lactate, and psychological measures. Conclusions: CHO mouth rinsing enhanced running performance significantly more when participants were dehydrated vs. euhydrated due to the greater sensitivity of oral receptors related to thirst and central mediated activation. These results show that level of dehydration alters the effect of brain perception with presence of CHO.